2015
DOI: 10.3109/09273948.2015.1005240
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Scleritis: Analysis of Epidemiology, Clinical Factors, and Risk of Recurrence in a Cohort of 114 Patients

Abstract: Posterior scleritis is an uncommon disease causing pain and visual loss. In around 40% of the cases, it can be associated with other systemic diseases. Median time to relapse was 210 days. Relapses may occur in around 1 in 3 patients, with an incidence rate of 15.81% per person/year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
92
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 22 publications
5
92
2
Order By: Relevance
“…Posterior scleritis may be challenging to diagnose in certain cases as it may present clinically with a subretinal mass due to the localization of the underlying scleral inflammation to a part of the sclera; hence, a wide list of differential diagnoses should be examined thoroughly before reaching a conclusion and proceeding with the treatment 2-7. Posterior scleritis most commonly presents with periocular pain, which is reported to occur in 64% of the cases, unlike our patient, who presented without pain 5. Few studies in the literature have reported a presentation similar to that of our patient, where posterior scleritis manifested clinically as a subretinal mass, mimicking the appearance of intraocular tumors, such as amelanotic choroidal melanoma; however, ultrasonographic evaluation helped limit the differential diagnosis 3,6,9,10.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Posterior scleritis may be challenging to diagnose in certain cases as it may present clinically with a subretinal mass due to the localization of the underlying scleral inflammation to a part of the sclera; hence, a wide list of differential diagnoses should be examined thoroughly before reaching a conclusion and proceeding with the treatment 2-7. Posterior scleritis most commonly presents with periocular pain, which is reported to occur in 64% of the cases, unlike our patient, who presented without pain 5. Few studies in the literature have reported a presentation similar to that of our patient, where posterior scleritis manifested clinically as a subretinal mass, mimicking the appearance of intraocular tumors, such as amelanotic choroidal melanoma; however, ultrasonographic evaluation helped limit the differential diagnosis 3,6,9,10.…”
Section: Discussionmentioning
confidence: 78%
“…Few studies in the literature have reported a presentation similar to that of our patient, where posterior scleritis manifested clinically as a subretinal mass, mimicking the appearance of intraocular tumors, such as amelanotic choroidal melanoma; however, ultrasonographic evaluation helped limit the differential diagnosis 3,6,9,10. Such studies highlight the importance of B-scan or Amplitude scan as crucial diagnostic tests 4,5. Delayed diagnosis may mislead treatment, and expose the patient to vision-threatening and possibly life-threating complications if the underlying systemic illnesses are not diagnosed early in the course of the disease 4…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations